Combined effect of oxygen enrichment and exhaust gas recirculation on the performance and emissions of a diesel engine fueled with biofuel blends. Issue 1 (2nd January 2018) - Dinesha, P.; Mohanan, P.
ABSTRACT: The present study investigates the combined effect of oxygen enrichment and exhaust gas recirculation (EGR) on the performance and emission characteristics of a cardanol biofuel blend, namely B20M10 (20% cardanol, 70% diesel and 10% methanol by volume). The tests are conducted on a four-stroke single-cylinder diesel engine at different loading conditions. Intake air is enriched by 7% of the atmospheric oxygen concentration and exhaust gas is recirculated by 10, 15 and 20% of the total intake charge. Research results reveal that the oxides of nitrogen (NOx ) emission decreases as the percentage of EGR increases from 0 to 20%. The results shows 11.8% lower NOx B20M10 at 7% oxygen enrichment and 20% EGR when compared to B20M10 without oxygen enrichment and 0% EGR. Higher carbon monoxide (CO), unburnt hydrocarbon (HC) and smoke, and lower brake thermal efficiency are obtained for higher EGR percentages. From the studies it can be stated that B20M10 cardanol biofuel blend with 7% intake air oxygen enrichment and 15% EGR shows better reduction in NOx emissions with minimum penalty of performance and other emission characteristics.